2021
DOI: 10.1007/s00109-021-02120-z
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing the power of NK cells in anticancer immunotherapy

Abstract: Due to their physiological role in removing damaged cells, natural killer (NK) cells represent ideal candidates for cellular immunotherapy in the treatment of cancer. Thereby, the cytotoxicity of NK cells is regulated by signals on both, the NK cells as well as the targeted tumor cells, and the interplay and balance of these signals determine the killing capacity of NK cells. One promising avenue in cancer treatment is therefore the combination of NK cell therapy with agents that either help to increase the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 111 publications
(126 reference statements)
0
12
0
Order By: Relevance
“…A large variety of new drugs able to enhance NK cell response are being tested in clinical trials, but a toxic effect has been reported for some of them ( 42 , 43 ). Development of small molecules targeting ERAP1 might provide an innovative tool to improve outcome of NK cell-based antitumor therapy protocols.…”
Section: Discussionmentioning
confidence: 99%
“…A large variety of new drugs able to enhance NK cell response are being tested in clinical trials, but a toxic effect has been reported for some of them ( 42 , 43 ). Development of small molecules targeting ERAP1 might provide an innovative tool to improve outcome of NK cell-based antitumor therapy protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Based on high NK cell frequencies and high prevalence of tumor formation in the FRT, strategies for increasing tumor recognition by NK cells have been discussed. This includes the sensitizing of tumor cells for NK cell killing, improving the cytotoxicity of NK cells ex-vivo via cytokine treatment or the generation of tumor-specific NK cells generated via genetic engineering using chimeric antigen receptor (CAR)-expressing NK cells [ 75 , 76 ].…”
Section: Tissue-resident Immunity In the Endometriummentioning
confidence: 99%
“…Considering these immune evasion mechanisms, various strategies to enhance NK cell function have been developed (4,(37)(38)(39). Research into the optimal selection and dosing regimes of cytokines used for expansion and activation (39)(40)(41)(42) has identified IL-15 as the preferred choice (43), while work on membrane bound IL-15 and IL-21 has also shown advantages (44)(45)(46).…”
Section: Enhancing Nk Cell Functionmentioning
confidence: 99%
“…Despite engineered T cell therapies advancing through clinical trials to commercialization (1), some major challenges remain such as high rates of serious adverse side effects, production inefficiencies, and high costs for autologous treatment generation (2). Recent research has shown that NK cells can overcome these challenges to develop into an independent or complementary class of cancer immunotherapies (3)(4)(5)(6). A complementary field benefiting from advances in NK cell development is that of NK cell extracellular vesicles (NKEVs), with purified NKEVs having proven to reproduce key functions of their parent NK cells (7).…”
Section: Introductionmentioning
confidence: 99%